School counsellor's roles in minimising adolescents' attrition from schools - Aluede, Oyaziwo (2003)
Counselling ways (rendering financial advice, providing encouragement, reassurances and support), which the school counselllors could adopt to help the school system minimize the increasing incidence of school dropout, were advanced.